Fascioliasis: A Zoonotic Disease and Diagnostic Capture Using Radiological Imaging - Rengganis, Anggraeni Ayu; Awaludin, Aan; Nugraheni, Yudhi Ratna (Universitas Airlangga, 2024)
Fascioliasis, also known as hepatic distomatosis or fasciolosis, is a zoonotic infection caused by the trematodes of Fasciola. The usual reservoir for this parasitic disease is herbivorous mammals, including humans, sheep, goats, and cattle. However, humans can contract this zoonosis infection by ingesting metacercaria, a juvenile trematode stage, which adheres to aquatic vegetation. Fascioliasis is typically present asymptomatically. However, human fascioliasis may have symptoms such as eosinophilia, abdominal discomfort, and various corroborative findings covering multiple diagnostic modalities. These diagnostic options include parasitological fecal examination, which observes the parasite in the feces; radiological imaging techniques, which envision the anatomical abnormalities created by the invasion; and serological studies, which could detect the immune response system to the infestation of the parasite. This review article aims to characterize fascioliasis in terms of zoonotic occurrence, outline the available diagnostic modalities, and highlight the specific significance of radiological imaging. This may contribute to the timely and adequate identification of the condition. This review article may contribute to forming the professional dialogue concerning fascioliasis, including its epidemiology, clinical presentation, and differential diagnostics